PSYCHOLOGICAL DOMINANCE, MARKET DOMINANCE AND THEIR IMPACTS IN TURKEY - Bildirici, Melike; Parasiz, Ilker; Ersin, Ozgur Omer; Aykac-Alp, Elcin (EDITURA ASE, 2015)
The study focuses on analyzing an economy that applies an inflation-targeting rule in which the policy interest rate is determined actively by the Taylor rule, and the policy maker involuntarily becomes the affirmant of inflation. In an economy that applies inflation-targeting policy where interest rates are determined in light of the Taylor rule, as the Central Bank tries to establish price stability and financial stability by determining policy interest rates, the Central Bank might fall into a position to do nothing but to assent inflation. In the empirical section, two new indices, the psychological dominance (pdi) and market dominance indices (mdi) are developed based on the difference between the policy rates. The band within which the indices follow random walk processes are determined with Band-TAR models. The CB policy is additionally modeled with a nonlinear Taylor rule with TVEC models. The most significant point of the process is its inflation-creating effect. By moving from the Turkey example, the main problem in the policies of Central Bank of Turkey is the difference between the borrowing and lending rates and its inflationary effect.
Keywords: Price Stability; Monetary Policy; Central Bank; Taylor Rule; Nonlinear econometrics; MONETARY; Business & Economics; Mathematics